Odpowiedzi

2010-03-04T15:48:49+01:00
A.
-3x=2x-10
-5x=-10 /:(-5)
x=2

b.
2x-2=7-x
3x=9 /:3
x=3

c.
10=4-2x
2x=-6 /:2
x=-3

d.
-(2x-1)=4
-2x+1=4
-2x=3 /:(-2)
x=-1½

e.
2(x+1)=6
2x+2=6
2x=4 /:2
x=2

2.
a.
0,1x+0,2=-0,3
0,1x=-0,5 /:0,1
x=-5

b.
0,25x+0,4=0,35
0,25x=-0,05 /:0,25
x=-0,2

c.
1-0,2x=-0,3
-0,2x=-1,3 /:(-0,2)
x=6,5

d.
0,01x-1=0,1x-0,1
-0,9x=0,9 /:(-0,9)
x=-1
2010-03-04T15:48:50+01:00
1. a) -3x = 2x-10
10=5x \:5
2=x

b)2x-2=7-x
3x=9 \:3
x=3

c)10=4-2x
2x=-6 \:2
x=-3


d)-(2x-1)=4
-2x+1=4
-3=2x \:2
-1,5=x

e)2(x+1)=6
2x+2=6
2x=4 \:2
x=2

2.a)0,1x+0,2=-0,3
0,1x=-0,5 \*10
x=-5

b.0.25x+0,4=0,35
0,25x=-0,05 \*4
x=-0,2

c.1-0,2x=-0,3
1,3=0,2x \*5
6,5=x

d.0,01x - 1 = 0,1x - 0,1
-0,9=0,09x \*100
-90=9x \:9
-10=x
2010-03-04T15:51:37+01:00
1.
a.
-3x=2x-10
-3x-2x=-10
-5x=-10/:(-5)
x=2

b.
2x-2=7-x
2x+x=7+2
3x=9/:3
x=3

c.
10=4-2x
2x=4-10
2x=-6/:2
x=-3

d.
-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/:(-2)
x=-3/2
x=-1 i 1/2

e.
2(x+1)=6
2x+2=6
2x=6-2
2x=4/:2
x=2

2.
a.
0,1x+0,2=-0,3
0,1x=-0,3-0,2
0,1x=-0,5/:0,1
x=5

b.
0.25x+0,4=0,35
0,25x=0,35-0,4
0,25x=-0,05/: 0,25
x=-0,2

c.
1-0,2x=-0,3
-0,2x=-0,3-1
-0,2x=-1,3/: (-0,2)
x=6,5

d.
0,01x-1=0,1x-0,1
0,01x-0,1x=-0,1+1
-0,09x=0,9/:(-0,09)
x=-10